MANTRA TIPONG TAWAR DALAM TRADISI UPACARA PERTANIAN DAYAK PASER SEBAGAI PROYEKSI KEHIDUPAN MASYARAKAT - Rika Istianingrum; Retnowaty Retnowaty (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2018)
[Title: Tipong Tawar Mantra in the Tradition of Agricultural Ceremony of Dayak Paser as a Projection of Community Life] Mantra as one of the genre of oral literature, in its time used by society archipelago as the answer to handle life problems. Mantra in a tradition of society that its trace has been found nowadays is a manifestation of the efforts and ways of community groups in understanding and explaining the reality of the environment. Tipong Tawar mantra is one of the spells that developed in the Dayak tribe Paser East Kalimantan. This mantra is used in Dayak Paser traditional agricultural ceremony. The purpose of this research was to understand the values of the function of the Tipong Tawar mantra in the tradition of Dayak agricultural ceremony of Paser as the life projection of Dayak people in East Kalimantan. The type of research used in this study was qualitative. This research used descriptive method and ethnographic approach. Data collection techniques were done through interviewing, recording, and notetaking. The findings showed that the use value or function of mantra in the life of Dayak Paser community is as a projection system of society, as the validity of social norms, as an educational tool, as a justified giver of society or problem-makers.